Complications of conservativa splenic surgery in trauma.: Three cases. - Puig, Roberto; Harretche, Martín; Ferreira, Ciro; Lerena, Ana; Liard, Washington; Pizzarossa, Carlos (Cirugía del Uruguay, 1987)
25 cases of splenic trauma were seen in the las! years. 6 splenectomles and 19 conservatlve procedures were performed. 3 cases that had evolutive compllcations were analyzed, concluding t.hat these no related with the procedure. The value of ultrasound for diagnosis, evolutiva control, detection of compllcations and identication of intact remnant parechyma is pointed out. A review of morbidity and mortality bibliography is done.